2015 41st Euromicro Conference on Software Engineering and Advanced Applications 2015
DOI: 10.1109/seaa.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Test Reuse for Embedded Systems: A Systematic Mapping Study

Abstract: Abstract-Vertical test reuse refers to the the reuse of test cases or other test artifacts over different integration levels in the software or system engineering process. Vertical test reuse has previously been proposed for reducing test effort and improving test effectiveness, particularly for embedded system development. The goal of this study is to provide an overview of the state of the art in the field of vertical test reuse for embedded system development. For this purpose, a systematic mapping study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Systematic mapping studies are recommended methods for getting a broad understanding of a research topic and does not involve detailed synthesis as in the case of a systematic literature review (see e.g. [25], [26]). Our methodology is driven by using a predefined protocol that aims to be unbiased by being auditable and repeatable [27].…”
Section: Research Methodology a Systematic Mapping Studymentioning
confidence: 99%
“…Systematic mapping studies are recommended methods for getting a broad understanding of a research topic and does not involve detailed synthesis as in the case of a systematic literature review (see e.g. [25], [26]). Our methodology is driven by using a predefined protocol that aims to be unbiased by being auditable and repeatable [27].…”
Section: Research Methodology a Systematic Mapping Studymentioning
confidence: 99%
“…The work from Flemström [20] deals with a very specific research area: vertical test reuse for embedded systems. They defined vertical reuse as the reuse of artifacts over different integration levels during the engineering process.…”
Section: Related Workmentioning
confidence: 99%
“…Even though similarities, both within and among test cases, can be identified, our previous study (Flemström et al 2015) showed that these overlaps can be scattered all over the set of test cases and could not be trivially removed. Further, the study indicated that test cases seldom overlap entirely.…”
Section: Introductionmentioning
confidence: 92%